Solid‐State NMR‐Driven Crystal Structure Prediction of Molecular Crystals: The Case of Mebendazole. Issue 6 (28th December 2021) - Bravetti, Federica; Bordignon, Simone; Alig, Edith; Eisenbeil, Daniel; Fink, Lothar; Nervi, Carlo; Gobetto, Roberto; Schmidt, Martin U.; Chierotti, Michele R.
Abstract: Among all possible NMR crystallography approaches for crystal‐structure determination, crystal structure prediction – NMR crystallography (CSP‐NMRX) has recently turned out to be a powerful method. In the latter, the original procedure exploited solid‐state NMR (SSNMR) information during the final steps of the prediction. In particular, it used the comparison of computed and experimental chemical shifts for the selection of the correct crystal packing. Still, the prediction procedure, generally carried out with DFT methods, may require important computational resources and be quite time‐consuming, especially if there are no available constraints to use at the initial stage. Herein, the successful application of this combined prediction method, which exploits NMR information also in the input step to reduce the search space of the predictive algorithm, is presented. Herein, this method was applied on mebendazole, which is characterized by desmotropism. The use of SSNMR data as constraints for the selection of the right tautomer and the determination of the number of independent molecules in the unit cell led to a considerably faster process, reducing the number of calculations to be performed. In this way, the crystal packing was successfully predicted for the three known phases of mebendazole. To evaluate the quality of the predicted structures, these were compared to the experimental ones. The crystal structure of phase B of mebendazole, in particular, was determined de novo by powder diffraction and is presented for the first time in this paper. Abstract : Make it faster ! A combined Crystal Structure Prediction – NMR crystallography (CSP NMRX) approach is presented for solving the structures of the three polymorphs, A, B, and C, of mebendazole. These are characterized by three different tautomeric forms, that is, they are desmotropes. The predicted structures show perfect overlapping with the experimental ones, with that of form B solved de novo from powder X‐ray diffraction.